THE MAIN DYNAMIC INDICATORS OF PASSENGER CARS - Fiediushyn, Yu. M.; Pshinko, O. M.; Myamlin, S. V.; Donchenko, A. V.; Loboiko, L. M. (Science and Transport Progress, 2005)
In article the description of the basic dynamic parameters of quality of the carriage and its influence on a way is resulted. And also the algorithm of an estimation of stability of movement on Lyapunov is described.